KEJAHATAN KEKERASAN DALAM PERSPEKTIF KRIMINOLOGI - Erniwati Erniwati (Fakultas Syariah UINFAS Bengkulu, 2015)
Crime and Violent in Criminology Perspective:The act of violent in the society is isformed in various type of crimes, according to its chronological or in conservative form and modernform. It is of interest to criminologist to exemine the meaning of crime and violent in crimonologyperspective wether according to law or non law as well as the meaning of crime and violent accordingto the experts starting from the understanding of crime and violent, the forms of violent, and it’sgroups, it will start from the Act No. 23 year 2004 about abolishing the violent in the household uptothe harsh crime and violent such as phisical violent, sexual harassment and the neglect of household,of which very common in the family and the society, the act of physical violent e.g: Looting, Killing,and the act of sexual crime, e.g: sexual harassment, rape, etc. The paper will further explain about thefactors and the dynamics of violence in society